A flexible and adaptive Simpler GMRES with deflated restarting for shifted linear systems. (1st August 2019) - Zhong, Hong-Xiu; Gu, Xian-Ming
Abstract: In this paper, two efficient iterative algorithms based on the Simpler GMRES method are proposed for solving shifted linear systems. To make full use of the shifted structure, the proposed algorithms utilizing the deflated restarting strategy and flexible preconditioning can significantly reduce the number of matrix–vector products and the elapsed CPU time. Numerical experiments are reported to illustrate the performance and effectiveness of the proposed algorithms.